Níveis de imunoglobulina A salivar, ansiedade, estresse e depressão de mulheres mastectomizadas em uso de tamoxifeno - Olympio, Paula Cristina de Andrade Pires (2008)
This study seeks to evaluate the psychoneuroimmunological basis of women who after having undergone mastectomies were submitted to hormonotherapy using salivary immunoglobulin A (IgAs) as an immunological marker. The study concerns a random laboratory trial composed of a sample of 55 women, which was performed at the Rehabilitation Program for Women with Mastectomies (PREMMA) at the oncology clinic of Dr. Ylza Bianco and at the reception area of the chemotherapy ward at the Santa Rita de Cássia Hospital, Vitória, Espírito Santo, Brazil. The goal of this trial was to evaluate the level of IgAs of mastectomized women submitted to hormonotherapy and to examine the correlation between the IgAs of those women, taking into account variables such as age, smoking habits, alcohol consumption habits, types of breast carcinoma, degree of cancer progression, signs and symptoms of stress, traces of anxiety, states of anxiety, and signs and symptoms of depression. Data with respect to these variables were collected by means of an interview (the information annotated in reports), the State-Trait Anxiety Inventory (IDATE in Portuguese), the list of signs and symptoms of stress (LSS/VAS), and the Edinburgh Postnatal Depression Scale (EPDS). The trial employed immunoturbidimetry in order to measure the levels of IgAs, collecting the saliva samples at two moments: before beginning the use of tamoxifen and three months after the treatment had started. The statistical methodology used in the study is the SPSS, version 13.0. It can be concluded from this study that there is no significant connection between the IgAs and the variables of age, smoking habits, alcohol consumption, types of breast carcinoma, signs and symptoms of stress, traces of anxiety and states of anxiety. However, there was a significant relationship between IgAs with signs and symptoms of depression and degree of cancer progression.